ISO 14000 تحديات الشركات الصناعية العربية في ظل نظام الإدارة البيئية : دراسة مستقبلية - الدكتور ميسر إبراهيم أحمد (PROSPECTIVE RESEARCHES, 2023)
The few passed years have witnessed international interests on the environment, its aspects and problems, these lead to unlimited numbers of seminars, symposiums and conferences on the national, regional and international level. These encourage many international organizations whose interest on Quality management and Environmental Management to prepare for a series of International Standards about E.M., like those which concentrates on Quality Management. This paper attempts to discuss three axes which are: ISO 14000 Identification and reasons for creating. ISO 14000 Contents (14001,14004). Analysis of Arabic situation and Arabic Industrial Companies attitudes. At the end the paper suggests some practical indicators which help many relevant sides to put the first steps towards EMS (Environmental Management System) Applications.